Translation and Translatio: 'nuestro latín' in Alfonso el Sabio's General estoria. Issue 5 (27th May 2016) - Ekman, Erik
Abstract: One of the more puzzling aspects of lexical gloss in the General estoria of Alfonso X is the use of the phrase nuestro latín, which is unique to the General estoria within the Alfonsine corpus. Since Antonio Solalindés study of it in 1936, the phrase has been taken to indicate a vague distinction between Latin and the vernacular. However the term latín has important historiographic implications apart from denoting the Latin language, and nuestro latín is one of several first person plural phrases unique to the General estoria that refers to language, exegesis or doctrine, such as nuestro romanz, nuestro language, nuestros sabios and nós los christianos . This paper examines the use of these first person plural phrases in lexical glosses as historiographic phenomon. Nuestro latín and other first person plural phrases in the General estoria separate Christian Castile from Muslim, Jewish and pagan others while casting Alfonso, his text and his readers as inheritors of imperial authority by establishing ownership of and affiliation with a Latin past.